What explains the concentration of off-premise alcohol outlets in Black neighborhoods?. (December 2020) - Lee, Juliet P.; Ponicki, William; Mair, Christina; Gruenewald, Paul; Ghanem, Lina
Abstract: Introduction: Greater availability of commercial alcohol is associated with increased alcohol use and related public health problems. Greater alcohol outlet density, a marker of alcohol availability, is associated with poorer and predominantly minority neighborhoods. However, poorer populations, African Americans, and Latinxs report using less alcohol compared to Whites and wealthier groups. We consider the role of structural racism in the social ecology of alcohol availability. Specifically we examine racist urban land use practices in the USA which became codified in the 1930s through Federal Home Owner Lending Corporation (HOLC) designations for assigning parcel values, known as "redlining." Redlining demarcated low-density residential zones for wealthy Whites which excluded poor and non-White people as well as certain businesses, including alcohol retailers. We assessed the impacts of historic redlining on present day risks for exposure to retail alcohol availability in urban Northern California. Methods: For six contiguous and demographically diverse Northern California cities we obtained digital renderings of HOLC maps (1937) which demarcated exclusions of people and businesses for 119 neighborhood areas across four land valuation zones. We then identified the most prevalent HOLC rating for each of 520 current Census block groups in the six cities, including a residual category for areas not rated by HOLC. We geolocated all current (2016) off-premise alcohol sales outlets operating in the six cities (N = 401). We used Bayesian spatial Poisson models to relate current alcohol outlet densities and Census-based estimates of neighborhood characteristics to historic HOLC classifications. Results: Spatial Poisson analyses found far greater contemporary off-premise outlet densities in the lowest-valued HOLC zones than in the highest (median relative rate [RR] 9.6, 95% CI 4.8–22.1). The lowest-valued HOLC zones were also characterized by far higher current percentages of both Black residents (RR 30.4, 95% CI 17.0–54.6) and Hispanic residents (RR 9.7, 95% CI 7.2–12.9). Conclusions: Present day risks for exposure to retail alcohol availability were delimited by historic exclusionary land use practices. Current inequitable health risks may be founded on racist spatial projects of past decades. Highlights: Planning and zoning created neighborhoods across the SF Bay Area in which non-wealthy, non-White people and density of alcohol retailers and housing were excluded or allowed. Structural racism measured by historic federal land valuation zones predicted the collocation of off-premise alcohol outlet density with lower income and non-White residents. Historical socio-political contexts must be considered in the assessment and interpretation of social-ecological characteristics which shape population health.